(untitled) (Scientific journal of the Fergana State University, 2024)
This article highlights the role of folk medicine in primitive religions based on field research. The use of folk medicine in the customs and religious views of the Uzbek people was analyzed on the example of the religious views of the residents of Jizzakh region. We can see that the aspects related to medicine in some elements of primitive religions are still preserved in the daily life of the inhabitants of some remote rural areas of our country, and there are believers in various beliefs related to them. In today’s era of advanced science, the elements of medicine in religious views are gaining an important place in the life of society.